Information technology and global sourcing - Philippe Fromenteau (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2016)
This paper examines how IT influences global sourcing decisions. It develops a theoretical model to study how IT determines the decisions of firms located in the high-wage North whether to offshore production to a low-wage country in the South. Offshoring to South however is subject to costly communication reflected by partially incomplete contracting. More sophisticated IT allows more efficient communication between the Northern headquarter and its Southern intermediate input supplier and alleviates contractual frictions. The model provides several predictions about the impact of IT on the organization of the global supply chain. Complex industries for which codifiability and verifiability of information is a much harder task, are more likely to source intermediate inputs in countries with more efficient IT infrastructure. Considering the mode of firm organization, more efficient IT infrastructure is expected to reduce the share of intra-firm trade in more complex industries. These predictions are examined and validated using disaggregated industry-level trade data. Most importantly, these findings are robust to controlling for well-known sources of comparative advantage and determinants of firm organization such as factor endowments, financial development and contract enforcement.
urn:nbn:de:bvb:19-epub-29631-7
Keywords: D23; F14; F23; L23; O33; 330; Information Technology; Global Sourcing; Multinational Firm; Firm Organization; Tasks